2012
DOI: 10.1371/journal.pone.0046258
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Organic Compounds in Uremia

Abstract: BackgroundAlthough “uremic fetor” has long been felt to be diagnostic of renal failure, the compounds exhaled in uremia remain largely unknown so far. The present work investigates whether breath analysis by ion mobility spectrometry can be used for the identification of volatile organic compounds retained in uremia.MethodsBreath analysis was performed in 28 adults with an eGFR ≥60 ml/min per 1.73 m2, 26 adults with chronic renal failure corresponding to an eGFR of 10–59 ml/min per 1.73 m2, and 28 adults with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 18 publications
1
41
0
Order By: Relevance
“…A recent study by Pagonas et al employs IMS coupled to a MCC, to identify specific VOC in patients with ESRD before and after hemodialysis [128]. Several compounds such as ammonia, hydroxyacetone and 3-hydroxybutanone, were significantly increased in ESRD patients as opposed to healthy volunteers.…”
Section: Uremic Fetormentioning
confidence: 99%
“…A recent study by Pagonas et al employs IMS coupled to a MCC, to identify specific VOC in patients with ESRD before and after hemodialysis [128]. Several compounds such as ammonia, hydroxyacetone and 3-hydroxybutanone, were significantly increased in ESRD patients as opposed to healthy volunteers.…”
Section: Uremic Fetormentioning
confidence: 99%
“…10,14 A recent study showed that ammonia concentrations in the breath also are increased in chronic renal failure not requiring dialysis. 18 In 1977, Simenhoff et al 17 already found that, apart from ammonia, trimethylamine (TMA) and dimethylamine (DMA) underlie the fishy odor in uremia. TMA and DMA are aliphatic amines, boiling between -61C and -71C, thus being highly volatile.…”
Section: In the Breathmentioning
confidence: 99%
“…It confirmed the findings on ammonia and DMA/TMA as described earlier. 18 Moreover, the study showed that 3-hydroxy-2-butanone (acetoin) and hydroxyacetone accumulated with decreasing renal function and were eliminated by dialysis. 3-Hydroxy-2-butanone is an organic compound generated primarily by bacteria and plants.…”
Section: In the Breathmentioning
confidence: 99%
See 2 more Smart Citations